2011
DOI: 10.1007/s13312-011-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infection and pneumonia in India: A systematic review of literature for advocacy and action: UNICEF-PHFI series on newborn and child health, India

Abstract: The systematic review summarizes current evidence on childhood ARI and pneumonia management and provides evidence to inform child health programs in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
77
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 95 publications
12
77
1
Order By: Relevance
“…Recent systematic reviews of childhood pneumonia etiology suggest that in developing countries, a few bacteria (S. pneumoniae and H. influenzae) and viruses (respiratory syncytial virus, influenza virus) are associated with majority of childhood CAP. 3,5,[10][11][12] A systematic review from India suggested that about 15-24% of bacterial pneumonia in South Asian countries can be attributed to S. pneumonia. 13 Accurate, reliable and rapid determination of etiology in childhood CAP is important because it would influence individual treatment decisions, antibiotic policy in the community, and also rational immunization policy at a national level.…”
mentioning
confidence: 99%
“…Recent systematic reviews of childhood pneumonia etiology suggest that in developing countries, a few bacteria (S. pneumoniae and H. influenzae) and viruses (respiratory syncytial virus, influenza virus) are associated with majority of childhood CAP. 3,5,[10][11][12] A systematic review from India suggested that about 15-24% of bacterial pneumonia in South Asian countries can be attributed to S. pneumonia. 13 Accurate, reliable and rapid determination of etiology in childhood CAP is important because it would influence individual treatment decisions, antibiotic policy in the community, and also rational immunization policy at a national level.…”
mentioning
confidence: 99%
“…12 A metaanalysis of ARI among under 5 children based on 12 Indian studies conducted since 1994, estimated incidence rates between 2.4 to 7.4 episodes per child per year and also highlighted the lack of community based studies on etiology of ARI from pneumonia. 13 In developing countries like India on an average every child has five episodes of ARI / year accounting for 30% -50% of total pediatric outpatient visits and 20-30% of pediatric admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia deaths account for approximately onefourth of the total deaths in under-five children, in India. [1] ARI is also an important cause of morbidity in the children across world, with an average about 5 episodes of ARI per child per year so accounting for about 238 million attacks. Medical records of states with high infant mortality rate show that up to 13% of inpatient deaths in pediatric wards are due to ARI.…”
Section: Introductionmentioning
confidence: 99%